SOCIAL SKILL TRAINING DAN TOKEN ECONOMY PADA ANAK PRASEKOLAH DENGAN MASALAH EXTERNALIZING BEHAVIOR - Emma Fauziah Saragih (Smart Education, 2026)
Abstract: Externalizing behavior in preschool children is a common behavioral problem in early childhood education settings and may persist if not addressed at an early stage. This study aimed to examine the effectiveness of Social Skill Training combined with a Token Economy technique in reducing externalizing behavior among preschool children. The study employed a one-group pretestâ€“posttest experimental design. The participants consisted of five preschool children aged six years who exhibited characteristics of externalizing behavior. Behavioral assessment was conducted using the Indonesian version of the Child Behavior Checklist (CBCL), focusing on the aggressive behavior and attention problems domains. The intervention was delivered over eight sessions through modeling, role play, and behavioral reinforcement using a Token Economy system. Data were analyzed using the Wilcoxon Signed Rank Test. The results indicated a reduction in externalizing behavior scores among all participants, with a statistically significant difference between pretest and posttest scores (Z = âˆ’2.02; p < 0.05). These findings suggest that Social Skill Training combined with a Token Economy is effective in reducing externalizing behavior in preschool children. Keywords: externalizing behavior; social skill training; token economy; preschool children Abstrak: Externalizing behavior pada anak prasekolah merupakan permasalahan perilaku yang sering muncul di lingkungan pendidikan anak usia dini dan berpotensi berlanjut bila tidak ditangani sejak dini. Penelitian ini bertujuan untuk menguji efektivitas Social Skill Training yang dikombinasi dengan Token Economy dalam menurunkan externalizing behavior pada anak prasekolah. Penelitian ini menggunakan desain eksperimen one-group prestest-posttest. Jumlah partisipan dalam penelitian ini sebanyak lima orang anak prasekolah berusia 6 tahun, dengan karakteristik esternalizing behavior. Pengukuran dalam penelitian menggunakan instrumen Child Behavior Checklist (CBCL) versi Indonesia yang difokuskan pada domain agressive behavior dan attention problems. Intervensi diberikan selama delapan sesi, melalui kegiatan modelling, role play serta penguatan perilaku menggunakan Token Economy. Data dianalisis dengan uji Wilcoxon Signed ank Test. Hasil analisis menunjukkan adanya penurunan skor externalizing behavior pada ke enam partisipan yang terlihat dari perbebdaan signifikan antar skor pretest dan posttest (z= -2.02; p